L‐Rhamnosylation: The Solvent is the Solution. Issue 1 (8th December 2016) - Elferink, Hidde; Pedersen, Christian Marcus
Abstract : Herein we present a systematic study ofl ‐rhamnosylation. The influence of protective groups, reactivity, solvents and glycosylation method, i.e. catalytic versus promoted glycosylation, are studied. It was found that the selectivity can be controlled to a large extend, by varying these parameters and hence the same donor can give both anomers. A reversal of the influence of the participating solvents is observed, and hence ethereal solvents increase the β selectivity, whereas nitrile solvents give almost exclusive α‐selectively. Abstract : The selectivity in rhamnosylation can be tuned by solvents or additives. Etheral solvents give more of the β products, while nitrile solvents give almost exclusively the α products.